Estrogen deficiency induces pelvic floor muscle atrophy via ERα/GLUT4 pathway - Xiaoyu Huang; Mengqi Zhou; Ying Wang; Mao Chen; Ya Xiao; Lingyun Li; Fangyi Zhu; Liying Chen; Xiaoyu Tian; Shiman Wu; Bingshu Li; Li Hong (PLoS ONE, 2026)
Pelvic floor dysfunction (PFD) is a common disease in women that seriously affects physical and psychological health. Menopause-associated estrogen reduction is one of the risk factors. However, the role and mechanism of estrogen in PFD remains unclear. In this study, we observed atrophy of both fast and slow muscle fibers in the pelvic floor muscle (PFM) of ovariectomized rats, accompanied by decreased expression of estrogen receptor α (ERα). Estrogen deficiency severely impaired the proliferation, differentiation, and mitochondrial function of C2C12 myoblasts and increased apoptosis, which could be rescued by ERα agonist. Mechanistically, estrogen deficiency led to the downregulation of ERα, which in turn suppressed the expression of glucose transporter 4 (GLUT4) and its trafficking regulator Rac family small GTPase 1 (RAC1). This disruption abolished the critical co-localization of GLUT4 with RAC1, resulting in defective glucose uptake, mitochondrial dysfunction, and ultimately impaired myoblast proliferation and differentiation. Both ERα activation and GLUT4 overexpression rescued these defects. Thus, our study delineates a novel ERα/GLUT4 pathway that mediates PFM atrophy under estrogen deficiency conditions, providing a potential therapeutic target for PFD.